Analisis Perilaku Kepemimpinan Kepala Sekolah, Kesejahteraan Guru dan Motivasi Kerja Guru terhadap Kinerja Guru di MAN Se-Kabupaten Blitar - Mashudi, Moh. (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2017)
Leadership behavior of principal, teacher welfare, and teacher work motivation are important to be implemented because it can affect teacher performance at MAN in Blitar Regency. This study examines the behavior of principal leadership, teacher welfare, and teacher work motivation on teacher performance at MAN in Blitar Regency. Population of this study is 170 teachers and taken as many as 114 teachers as sample through proportional random sampling method with table Isaac and Michael with 5% error rate. The results showed that partially the leadership behavior of principals have a significant positive effect on teacher performance at MAN in Blitar Regency. Variables of teacher welfare have a significant positive effect on teacher performance at MAN in Blitar Regency. Other results showed the teacher work motivation has a significant positive effect on teacher performance at MAN in Blitar Regency.